Using Biographical Research (or is it Auto/Biography?) to Illuminate Adult and Lifelong Learning: Contested and Illuminating Space - Linden West (Adult Education Research Conference, 2007)
This paper illustrates ‘the turn’ to biographical approaches in the study of adult learning and considers some contested issues in this ‘family’ of approaches. Especial attention is paid to issues of subjectivity and objectivity and the role of the researcher in shaping the subject (s) of her enquiry. However, the paper concludes by suggesting that, whatever the differences, such approaches offer unique and more holistic insights into the complexities of learning, lifewide and lifelong.